An accelerator scenario for a hard X-ray free electron laser combined with high energy electron radiography - 魏涛 李一丁 杨国君 庞健 李煜辉 李鹏 Joachim Pflueger 何小中 卢亚鑫 王科 龙继东 章林文 吴强 (Chinese physics C, 2016)
In order to study the dynamic response of the material and the physical mechanism of fluid dynamics, an accelerator scenario which can be applied to both hard X-ray free electron laser and high energy electron radiography is proposed. This accelerator is mainly composed of a 12 GeV linac, an undulator branch and an eRad beamline. In order to characterize a sample＇s dynamic behavior in situ and real-time with XFEL and eRad simultaneously, the linac should be capable of accelerating the two kinds of beam within the same operation mode. Combining in-vacuum and tapering techniques, the undulator branch can produce more than 10zl photons per pulse in 0.1% bandwidth at 42 keV. Finally, an eRad amplifying beamline with 1：10 ratio is proposed as an important complementary tool for the wider view field and density identification ability.